PENGARUH KEPERCAYAAN MEREK DAN KEBIJAKAN HARGA TERHADAP KINERJA PENJUALAN PRODUK UMKM DI KOTA BANDA ACEH - Nyak Umar; Mukhdasir Mukhdasir (Jurnal Sains Riset, 2022)
This study aims to determine the effect of brand trust and price policy on sales performance of MSME products in Banda Aceh City. The population of this study amounted to 17080 MSME business actors, and the sampling technique used the slovin technique so that 100 business actors were obtained as samples. The model used in this study is multiple linear regression analysis. The results showed that brand trust and price policy had a significant effect on sales performance of MSME Products in Banda Aceh City, it was proven that brand trust and price policy were factors that could affect sales performance, as evidenced by the results of research by 20.1% and the remaining 79.9% is explained by other variables outside of this research such as promotion policy, product quality, accessibility, product image and others. The results of statistical tests show that brand trust and price policy simultaneously have a significant effect on sales performance of MSME products in Banda Aceh City, with a value of FcountFtable (12,2353,090). And brand trust and price policy partially have a significant effect on sales performance of MSME Products in Banda Aceh City, with a tcount t table (4.183 and 2.886 1.984). Based on the results of multiple linear regression analysis, it can be seen that from the two variables studied , it turns out that the brand trust variable (X1) which has the greatest influence on sales performance on MSME products in Banda Aceh City, with a coefficient value of 0.265 and followed by the price policy variable (X2) has a coefficient value of 0.221.Keywords: Brand Trust, Pricing Policy and Sales Performance.